Technopreneurial SMART Web for Adolescent Breast Health Literacy - Irma Irma; Andi Kamal M. Sallo; Marlina Marlina; Marni Br Karo; Dewi Parwati; Wan Ismahanisa Ismail (Aptisi Transactions on Technopreneurship (ATT), 2026)
Local wisdom-based ecopreneurship competency is an entrepreneurial concept that focuses on sustainability and environmental preservation. This provides health workers with the opportunity to utilize local natural resources efficiently and in an environmentally friendly manner, while still maintaining local social and cultural aspects. This study aims to examine the effectiveness of the e-learning method through Media Bidan Elok in improving the ecopreneurship competency of midwifery students in South Sulawesi. The study used a One Group Pre-Test and Post-Test design with 150 students from four regions, Gowa, Makassar, Parepare, and Palopo. The analysis results showed a significant increase in ecopreneurship competency after using local wisdom-based learning media, as seen from the increase in the average score from 58.4 on the pre-test to 82.6 on the post-test. In addition, the effectiveness of learning varied based on the length of the participants' work experience, with the highest N-Gain Score in the group with 0-5 years of work experience (0.72) and the lowest in the 15-20 year group (0.60). These findings indicate that e-learning media integrated with local wisdom values is effective in improving the competence of midwifery students. However, an adaptive approach is needed for groups with longer work experience. This study provides recommendations for further development of technology-based and local culture-based learning methods that can effectively improve ecopreneurship competencies among midwifery students.